Enhanced Tolerance to Cold in Common Bean Treated with Biostimulant - do Rosário Rosa, Vanessa [UNESP]; Farias dos Santos, Anna Luiza [UNESP]; Alves da Silva, Adinan; Peduti Vicentini Sab, Mariana [UNESP]; Barcellos Cardoso, Flávio; Marin, Mario Antonio; de Almeida Silva, Marcelo [UNESP] (Springer Nature, 2021)
Plants exposed to suboptimal temperatures suffer damage to physiological processes, growth, development and yield. Acting as enhancers of physiological and metabolic performance of plants, biostimulants have been used to mitigate crop damage caused by abiotic stresses. This study aimed to determine which formulation and dosage of FH Attivus® biostimulant have the best effects on the development of bean plants exposed to suboptimal temperatures (<20 °C). The experiment was conducted in a greenhouse under suboptimal temperatures in a randomized block design with four replications and ten treatments, consisting of three formulations and dosages of the biostimulant, applied at V4 stage, besides a control without biostimulant application. Growth, physiological and biochemical variables were evaluated. The application of biostimulant made bean plants more tolerant to low temperatures by maintaining CO2 net assimilation rate (A) and increasing the activity of antioxidant enzymes. The relative chlorophyll content (SPAD index), PSII effective quantum yield of linear electron flux (ϕPSII), apparent electron transport rate (ETR) and photochemical extinction coefficient (qP) were higher in all treatments compared to the control, as well as the lowest values of A and ETR were observed in the control. In addition, the activities of all evaluated antioxidant enzymes were superior to the control at the lowest dosages of formulation 2, and at all dosages of formulation 3, indicating, in these treatments, greater protection of cells against oxidative damage. The use of biostimulant is, therefore, a management that makes plants less susceptible to low temperatures in the growing environment.
Keywords: Antioxidant enzymes; Growth stimulant; Phaseolus vulgaris L; Photosynthetic activity; Suboptimal temperatures